Unobtrusive touch‐free interaction on mobile devices in dirty working environments. Issue 5 (7th May 2018) - Chen, Yingjie Victor; Huynh, William; McGraw, Tim; Qian, Zhenyu Cheryl; Hassan, Raymond
Abstract: In this work, we propose a new mode of interaction using hand gestures captured by the back camera of a mobile device. Using a simple intuitive two‐finger picking gesture, the user can perform mouse click and drag‐and‐drop operations from the back of the device, which provides an unobstructed touch‐free interaction. This method allows users to operate on a tablet and maintain full awareness of the display, which is especially suitable for certain working environments, such as the machine shop, garage, kitchen, gym, or construction site, where people's hands may be dirty, wet, or in gloves. The speed, accuracy, and error rate of this interaction have been evaluated and compared with the typical touch interaction in an empirical study. The results show that, although this method is not, in general, as efficient and accurate as direct touch, participants still consider it an effective and intuitive method of interacting with mobile devices in environments where direct touch is impractical.